Hybrid Energy System Design of Micro Hydro-PV-biogas Based Micro-grid. (March 2017) - Nishrina,; Abdullah, A G; Risdiyanto, A; Nandiyanto, ABD
Abstract: Hybrid renewable energy system is an arrangement of one or more sources of renewable energy and also conventional energy. This paper describes a simulation results of hybrid renewable power system based on the available potential in an educational institution in Indonesia. HOMER software was used to simulate and analyse both in terms of optimization and economic terms. This software was developed through 3 main principles; simulation, optimization, and sensitivity analysis. Generally, the presented results show that the software can demonstrate a feasible hybrid power system as well to be realized. The entire demand in case study area can be supplied by the system configuration and can be met by ¾ of electricity production. So, there are ¼ of generated energy became an excess electricity.